Barriers to and enablers of the use of the Otology Questionnaire Amsterdam in clinical practice-a qualitative post-implementation study - J.T. Kraak; K. Verhoef; S.E. Kramer; P. Merkus (SpringerOpen, 2024)
Abstract Background The Otology Questionnaire Amsterdam (OQUA) is developed to evaluate multiple ear complaints and their impact on patients' daily lives. The current clinical use of this questionnaire is below the potential utilization. Aim To identify the barriers and enablers of using the OQUA as perceived by ENT surgeons and patients and provide recommendations for an implementation strategy. Methods Prospective and qualitative analysis was performed using focus groups and interviews with ENT professionals (n = 15) and patients (n = 25) with ear complaints of one tertiary referral hospital and two regional hospitals. Barriers and enablers were identified and classified by using the Capability-Opportunity-Motivation-Behavior model and the Theoretical Domains Framework. Suggestions for an implementation strategy will be made accordingly. Results ENT professionals' barriers included lack of knowledge and skills to use the OQUA, inadequate technological support and perceived time constraints during consultation, uncertainty about the clinical relevance and lack of feedback on the outcomes of the OQUA. Enablers included beneficial consequences of the OQUA for the professional, organization and science. Patients' barriers included lack of knowledge about the objective and usefulness of the OQUA, perceived burden, difficulties in completing the questionnaire and insufficient feedback during consultation. Patient enablers included beliefs about beneficial consequences of the OQUA for the patient, health care and society. Suggested interventions involved education, training, environmental restructuring and incentivisation. Conclusion Based on the findings, we propose an implementation strategy should focus on education and training about the objective, outcomes and relevance of the OQUA, environmental restructuring regarding the optimal use of the OQUA, and incentivisation with feedback on the valuable outcomes of the OQUA for the patient, professional and healthcare. Future research is needed to determine the feasibility of the implementation strategy.